SYSTEMATIC LITERATURE REVIEW : PENGARUH KEBIASAAN MEROKOK TERHADAP PENYAKIT JARINGAN PERIODONTAL PADA MASYARAKAT DI INDONESIA - Prasetyowati, Silvia; Puspitasari, Erika Putri; Soesilaningtyas, Soesilaningtyas (Jurnal Kesehatan Gigi dan Mulut (JKGM), 2022)
Background: Periodontal tissue is the tissue that surrounds the tooth and function as a support, smoking behavior is one of the causes of health problems in the periodontal tissue. Such as gingivitis, periodontitis. Periodontal disease is a dental and oral health problem wich has a fairly high prevalence in the community of 95.58%. Objective: To determine the kinds of diseases in the periodontal tissue caused by smoking in Indonesian society. Methods: Systematic literature review, data sources was by searching articles from the Google Scholar database, PubMed, Garuda Jurnal. Results: From the results of 10 literature review articles, it is known that there are several diseases of the periodontal tissue caused by smoking, such as periodontitis gingivitis.